Effect of Air Humidity in MIG Welded Joints on Tensile Strength and Impact Strength of Aluminum 5052 - Nduru, Fandi Bachtiar; Nugroho, Nur Yanu (BERKALA SAINSTEK, 2023)
In the shipbuilding process, delays often occur. In general, to speed up a ship's construction, overtime is carried out by workers until nighttime. Environmental conditions in a welding process, especially air humidity, strongly affect the properties of welded joints. The formation of hydrogen in the air caused by an inappropriate environment can cause defects in welded joints, especially porosity defects. Variations of welding environmental conditions used, are welding in the morning at 84% air humidity, daytime welding at 53% air humidity, and nighttime welding at 77% air humidity. This study aims to determine the material strength of air humidity variations during the welding process on the tensile strength and impact strength of 5052 aluminum material. This research uses experimental quantitative methods data analysis techniques used analysis of variance (ANOVA). The results showed that the higher the air humidity, the tensile and impact strength decreased. From the results of the tensile test, there is an influence of air humidity on the average value of tensile strength, where the highest value is found in the daytime welding variation specimen with 53% air humidity, worth 110.614 MPa. From the impact test results, there is an influence of air humidity on the average value of impact toughness, where the highest value is found in the daytime welding variation specimen with 53% air humidity, worth 89.42 J/mm2. From the ANOVA test results, the average tensile test and impact test have no significant differences.